2015
DOI: 10.1073/pnas.1413877112
|View full text |Cite
|
Sign up to set email alerts
|

Shadow enhancers enable Hunchback bifunctionality in the Drosophila embryo

Abstract: Hunchback (Hb) is a bifunctional transcription factor that activates and represses distinct enhancers. Here, we investigate the hypothesis that Hb can activate and repress the same enhancer. Computational models predicted that Hb bifunctionally regulates the even-skipped (eve) stripe 3+7 enhancer (eve3+7) in Drosophila blastoderm embryos. We measured and modeled eve expression at cellular resolution under multiple genetic perturbations and found that the eve3+7 enhancer could not explain endogenous eve stripe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 73 publications
4
58
0
Order By: Relevance
“…However, even if these interactions are not direct, the different responses of the proximal and distal enhancers to perturbation show that these enhancers use different regulatory logic, contradicting the initial picture of shadow enhancers as binding to the same set of TFs (Hong et al, 2008; Barolo, 2012). Our emerging picture is that shadow enhancers each build the same pattern in different ways; previous studies have shown that the snail shadow enhancers respond differently to a single repressor, (Dunipace et al, 2011), and in the eve locus, hb activates one shadow enhancer for stripe 7 and represses the other (Staller et al, 2015b). Here, we find an even more dramatic difference in the regulatory logic of the Kr shadow enhancers: each is activated by a non-overlapping set of TFs.…”
Section: Resultsmentioning
confidence: 99%
“…However, even if these interactions are not direct, the different responses of the proximal and distal enhancers to perturbation show that these enhancers use different regulatory logic, contradicting the initial picture of shadow enhancers as binding to the same set of TFs (Hong et al, 2008; Barolo, 2012). Our emerging picture is that shadow enhancers each build the same pattern in different ways; previous studies have shown that the snail shadow enhancers respond differently to a single repressor, (Dunipace et al, 2011), and in the eve locus, hb activates one shadow enhancer for stripe 7 and represses the other (Staller et al, 2015b). Here, we find an even more dramatic difference in the regulatory logic of the Kr shadow enhancers: each is activated by a non-overlapping set of TFs.…”
Section: Resultsmentioning
confidence: 99%
“…These “shadow” enhancers individually generate similar patterns of expression, but their combined expression levels are unpredictable (Bothma et al 2015; Dunipace et al 2011). We have shown previously that individual shadow enhancers can respond to different activators (Staller et al 2015; Wunderlich et al 2015). This suggests that shadow enhancers might work on different steps in transcription, in which case the kinetic model that we propose here could help to predict their combined activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that multiple cis-regulatory modules are often associated with genes and are co-acting [7881]. Some CRMs work concurrently to control spatial domains and levels of expression [82, 83], whereas others work sequentially to control the changing expression of genes in time [84].…”
Section: Key Challenges In Studying Spatiotemporal Regulation Of Genementioning
confidence: 99%